Introduksi Produksi Gula Aren Kristal Pada Perajin Gula Suka Maju Desa Batu Ampar Kabupaten Tanah Laut - Susi Susi; Tanwirul Millati (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
The development of palm sugar into crystalline palm sugar has the potential to be developed in order to substitute white sugar where the fulfillment is still quite a lot imported. Therefore, to increase the food security of sugar, it can be done by utilizing local palm sugar resources. Palm sugar production technology is quite applicable to be applied in rural areas and can be made from palm sap or palm sugar. The introduction of the processing of crystal palm sugar was carried out in the Suka Maju LSPBM Group with the stages of counseling, production skills training, packaging, hygienic production to obtaining a PIRT legality as Health Office permit. The quality of crystal palm sugar produced from several quality parameters was achieved including the water content of crystal palm sugar ranging from 2.38-2.70%, ash content 0.85-0.99%, sugar content 86.72%, yellowish brown color and in the form of crystals or powder. The crystal palm sugar products produced was under the brand name Sehati. The constraint was limitation of marketing because this product at the local level was still known only for the purpose of making cakes, as well as for the more expensive price of white crystal sugar. Need coaching and better links with related network to open up a better market. From the results of the analysis of the business of producing crystal palm sugar, it is feasible to run with a profit value of Rp. 24,007,100,00, the value of BEP was 892 kg, profitability of 0.55 and business efficiency of Return Cost Ratio (R/C) of 1.55